Capital mobility and costs of adjustment - Max Albert (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1989)
The paper considers intersectoral capital mobility in the context of investment theory. Convex costs of adjustment explain imperfect mobility of capital between sectors. Stocks of capital are endogenous; the model essentially is a twosector growth model with Keynesian investment functions. The paper analyzes adjustment in a small open economy with balanced and imbalanced trade and adjustment in a closed economy.
Keywords: 330